Abnormally Low Bid Criterion pada Pengadaan Jasa Konstruksi Proyek Pemerintah dengan Sistem Evaluasi Harga Terendah - Wibowo, Andreas; Christopher Leonaldo , Godjali (Jurnal Teknik Sipil, 2023)
Abstract This paper aims to determine the abnormally low bid criterion (ALBC) for evaluating bid prices in public construction procurement using the low-bid system based on empirical data sampled between 2016 and 2021. The ALBC values were calculated as the expected values of the first-order statistics generated by the Latin Hypercube simulation under an identically independent beta distribution, which was chosen based on the results of several goodness-of-fit tests. According to the correlation analysis, bid ratios are correlated with the number of bidders, which justifies using a specific bid ratio for a given number of bidders, if known. It has been demonstrated that ALBC decreases with the number of bidders and approaches the minimum bid ratio value asymptotically. This paper also proposes the 2.5 percentile lower bound value of the first-order statistics as the criterion for extremely low bids (ELBC). The simulation indicates that the ELBC and ALBC values are 69% and 83%, respectively. This paper also acknowledges the limitations of the study, which can serve as guidelines for continued studies. Keywords: Abnormally low bid criterion, extremely low bid criterion, first-order statistics, lowest bidding system, public procurement, Latin Hypercube Simulation.